Duality of orthogonal and symplectic random tensor models: general invariants - Keppler, Hannes; Muller, Thomas (Letters in mathematical physics, 2023)
In Gurau and Keppler 2022 (arxiv:2207.01993), a relation between orthogonal and symplectic tensor models with quartic interactions was proven. In this paper, we provide an alternative proof that extends to polynomial interactions of arbitrary order. We consider tensor models of order D with no symmetry under permutation of the indices that transform in the tensor product of D fundamental representations of O(N) and Sp(N). We explicitly show that the models obey the N to $$-N$$duality graph by graph in perturbation theory.